From Hartz IV to Bürgergeld: Reform preferences of the long-term unemployed - Fabian Beckmann; Rolf G. Heinze; Dominik Schad; Jürgen Schupp (DIW Weekly Report, 2022)
The German government is planning to reform Hartz IV by replacing it with a simpler and more accessible system known as Bürgergeld. Using a random-based survey of eight job centers in North Rhine-Westphalia, this Weekly Report considers the perspectives of the long-term unemployed: What do they think about the reforms? How do they perceive their situation? What are their daily lives like? The findings reveal the long-term unemployed have mostly positive, yet differentiated assessments of individual reform aspects. For example, a large majority of the long-term unemployed are in favor of improving opportunities for supplemental income and many are skeptical about a general ban on sanctions. Over 40 percent of the long-term unemployed report feeling "very" or "somewhat" ashamed of receiving means-tested basic security benefits, while nearly two thirds completely or somewhat agree with the statement that other benefit recipients are exploiting the system. According to their own statements, many benefit recipients are active in volunteer work and work around the neighborhood. Improving support for such informal work in the future can help strengthen the long-term unemployed's social participation beyond gainful employment. Moreover, due to inflation, a noticeable increase in the standard rate will be needed to mitigate poverty risks in the short and medium term. In addition, prolonging the sanctions moratorium could serve as a model project of sorts and provide insight into the effects of sanctions as well as an evidence-based assessment of the controversial topic. This opportunity should not go unused.
Keywords: D01; J28; J64; 330; transfer reform; long-term unemployment; preferences